The Future of 3D Printing in Medical Devices for Pediatric Care - Sven Harald; Magnus Erik (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
3D printing technology has revolutionized various sectors, including healthcare. This paper explores the role of 3D printing in the production of customized medical devices for pediatric patients. From prosthetics to surgical models, the study highlights how 3D printing can address specific needs in pediatric care, improving treatment outcomes and reducing costs. The paper also discusses future advancements and the potential for mass adoption in medical practices.